Precursory Physico-Chemical, Instrumental Evaluation and Acute Oral Toxicity Study of Purandara Vati - Lekshmi R Pillai; S.A Doddamani; Surekha S Medikeri (International Journal of Ayurveda and Pharma Research, 2024)
Purandara vati is a herbomineral formulation that has a promising effect on Shwasa, Kasa, and is nothing less than a Rasayana. The main ingredients are Parada, Gandhaka, Triphala, and Trikatu which is given Bhavana in Aja kshira. The current paper aims to evaluate the physicochemical parameter along with instrumental analysis followed by an acute oral toxicity study of Purandara vati. Materials and methods: Physicochemical, instrumental analysis of Purandara vati were conducted. An acute oral toxicity study was also conducted as per OECD 425 guidelines. The IAEC no of the study is FPS/IAEC/169/2024. The study was conducted with a total of 4 healthy female Wistar albino rats with 8–10-week-old (150- 180g body weight). Results: Purandara vati has shown a pH of 4.13, loss on drying 9.50%, total ash 4.32%, acid insoluble ash 2.36%, water soluble ash 2.66%. In XRD Purandara vati had showed mercury sulphide in the major phase. FTIR analysis identified various functional groups i.e., carboxylic acid, alkane, ester etc. Acute oral toxicity studies showed no mortality at a dose of 2000mg/kg body weight proving the fact that LD50 of Purandara vati is above 2000mg/kg. Conclusion: Purandara vati is a safe and potent herbomineral formulation.